INCREASED DURABILITY OF RESIN-DENTIN BONDS FOLLOWING CROSS-LINKING TREATMENT - Scheffel, Débora Lopes Salles (Oper Dent, 2015)
OBJECTIVES: This study evaluated the long-term effect of carbodiimide treatments of acid-etched dentin on resin-dentin bond strength of a simplified etch-and-rinse adhesive system. METHODS: Forty-eight sound third molars were divided into three groups (n=16) according to the dentin treatment: G1: Deionized water; G2: 0.5 mol/L 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) applied for 30 seconds; and G3: 0.5 mol/L EDC applied for 60 seconds. Flat dentin surfaces were produced, etched with 37% phosphoric acid for 15 seconds and then treated with deionized water for 60s or with 0.5 mol/L EDC for 30 or 60 seconds prior to the application of Single Bond 2. Crowns were restored with resin composite and beam specimens were prepared for microtensile testing. The beams from each group were tested 24 hours or 6 or 12 months after the adhesive procedures. One slab from each tooth was prepared and analyzed for nanolaekage. Bond strength (MPa) data were submitted to analysis of variance and Tukey test (α=0.05). RESULTS: The treatment of dentin with 0.5 mol/L EDC for 30 seconds (24.1±6.2 MPa) and 60 seconds (25.5±5.1 MPa) did not negatively affect the immediate bond strength of Single Bond 2 when compared to the control group (24.6±7.3 MPa). Additionally, EDC prevented resin-dentin bond degradation after 12 months in artificial saliva for both periods of treatment. An increased accumulation of silver ions was seen for the control group over time, while a much lower amount of silver grains was observed for the EDC-treated groups. CONCLUSIONS: 0.5 mol/L EDC was able to prevent resin-dentin bond degradation after 12 months, especially when applied for 60 seconds.